Effect and Strategies to Mitigate the Heat Stress on Buffalo Bull Reproduction - Arunpandian, J.; Srivastava, N.; Singh, G.; Gupta, S. K.; Kujur, A.; Aswini, G.; Jackson, A. (The Indian Journal of Animal Reproduction, 2021)
Heat stress (HS) is hazardous to the physiological functioning of reproductive organs, as well as for the optimum production of spermatozoa quality and quantity. During the summer animals suffer from HS due to an elevated environmental temperature causing increased testicular temperature resulting in accelerated free radicals generation. The mammalian spermatozoa are more vulnerable to free radical damage primarily because the sperm membrane contains cholesterol, sterols and polyunsaturated fatty acids. Certain levels of reactive oxygen species (ROS) are required for variety of physiological processes such as acrosome reaction, capacitation and fertilization. On the other hand, when the ROS levels are elevated, pathological condition are produced with the formation of lipid peroxidase, affecting the sperm membrane integrity and leads to leakage of intracellular contents. This is followed by abolished structural integrity, sperm motility and viability. As a result, during the summer, the volume of semen produced is low, with poor seminal characteristics. There are several methods to mitigate the HS of the animal such as physically constructing a shade, sprinkler and cooling fan, which facilitates conducive environment around the animals and help to reduce the heat stress. Moreover, certain semen additives can also be added to minimize the detrimental effects of HS post facto. The present review elucidates mechanism of HS genesis, changes occurring in spermatozoa morphology and amelioration of damaging effects of HS by application of various protocols.